Californium muriaticum for AIDS in Africa - Sherr, Jeremy (Homœopathic Links, 2013)
While attempting to determine the genus epidemicus of AIDS, one of the frequently needed remedies appears to be Californium muriaticum or Californium nitricum. This articles gives four case examples.
Keywords: HIV; AIDS; Epidemic diseases; Genus epidemicus; Californium muriaticum